Health Care Seeking Behavior in a Scheduled Tribe Community in India: A Mixed Methods Research Using the Framework of Andersen's Behavioral Model. (May 2021) - Podder, Debayan; Dasgupta, Aparajita; Dobe, Madhumita; Paul, Bobby; Bandyopadhyay, Lina; Pal, Arkaprovo
India's scheduled tribe population very often bears the brunt of inequity in accessing health care. The mixed-method research assessed the health care seeking behavior (HSB) of a tribal community residing in the eastern fringes of Kolkata metropolis. An adult, preferably the head, in 209 households was interviewed followed by qualitative interviews with relevant stakeholders. Conceptual framework of Andersen's behavioral model helped in identifying the potential predisposing, enabling, and need factors that influenced HSB. A total of 25.4% respondents reportedly sought informal care during last illness episode. Multivariable hierarchical-regression model (Nagelkerke R 2 = 0.381) showed that respondents' education level [adjusted odds ratio (AOR) = 2.52], household size (AOR = 3.14), nonenrollment to health insurance (AOR = 2.47), decision making by household head (AOR = 2.40), distance from the nearest urban primary health center (AOR = 3.18), and poor perception to illness severity (AOR = 2.24) were significantly associated to inappropriate HSB. Predominant health system barriers that emerged from qualitative interviews were irregular logistics, unfavorable outpatient timing, absence of female doctors, and nonretention of doctors at local urban primary health center. Community level barriers were poor awareness, self-medication practices, poor health insurance coverage, and poor public transportation. Recognition of these determinants may help in developing health promotion interventions tailored to their needs.